The Role of Digital Transformation in Enhancing Human Resource Management Practices in Global Organizations - Putri, Haliza Nabila; Mardani, Agnes Dini; Ardyansyah, Farid (Journal of Economics and Management Scienties, 2025)
This study explores the role of digital transformation (DT) in enhancing Human Resource Management Practices (HRMP) within multinational enterprises (MNEs). Employing a qualitative multi case study approach, data were collected through semi structured interviews, organizational documents, and digital implementation records across global companies. The research identifies four key areas of improvement due to digital tools: recruitment, training and development, performance management, and employee engagement. AI-based platforms, cloud based HRIS, and Learning Management Systems (LMS) have streamlined processes and enabled data driven decision making. However, the study also finds significant disparities in DT effectiveness across regions, influenced by infrastructure, digital literacy, and cultural factors. Critical organizational enablers such as digital leadership, employee digital competence, and strategic alignment were found to significantly mediate DT outcomes. The findings suggest that DT in HR should be approached holistically, integrating technology with strategic planning, change management, and ethical governance. This research contributes to the theoretical framework of digital HRM and provides practical insights for global HR leaders aiming to design adaptive and culturally responsive digital strategies. The study concludes that while digital tools offer significant potential, their success depends on organizational readiness and regional adaptability. Suggestions for future research include expanding the study to small and medium sized enterprises and analyzing sector specific dynamics.